ARTERIAL STRUCTURE AND HEALTH RELATED-PHYSICAL FITNESS IN MIDDLE AGES: SEDENTARY VS MARATHON RUNNERS - Lertsakul, Akaraseth; Chuensiri, Napasakorn; Suksom, Daroonwan (Journal of Sports Science and Health, 2021)
Purpose: To compare the vascular structure and health-related physical fitness between middle-aged sedentary and marathon runners. Methods: Twenty-two middle-aged male and female, aged between 3.80 ± 0.1 years, were assigned either to a sedentary group (n = 10, 4 male and 6 female) or a marathon runner group (n = 12, 8 male and 4 female). The marathon runners underwent the combined aerobic and resistance training program, 3 days per week for 2 weeks. Aerobic training program consisted of the interval, pace tempo and LSD run training, while BW resistance exercise comprised 4 sets of 15 repetitions of Squat, Leg lunge, and Calf raise. Vital sign, body composition, muscle performance, maximum aerobic capacity and vascular structure variables, including carotid intima-media thickness and arteries stiffness were measured pre-and post-intervention. Data was analyzed by using Independent t-test Pearson’s product moment at the statistical significance level of .05 and correlation. Results: Marathon runners had significantly lower body weight, resting heart rate, fat mass, carotid intima-media thickness and arteries stiffness than the sedentary (0.7%, 1.8%, 4.29%, 1.39% and 4.81%, respectively). They also had significantly higher leg muscle strength and endurance, 1RM squat, sit to stand, and maximum oxygen consumption than that in sedentary (6.44%, 10.04%, 12.14%, 10.08% and 7.81%, respectively). While the muscle mass was positively correlated with VO2max,the fat mass and percent fat were negatively correlated with VO2max. Conclusion: Sedentary behavior resulted in impairments in aerobic performance, muscle endurance, and muscle strength. but marathon runners had greater vascular structure, function and health-related fitness than the sedentary. The body composition was well correlated with the maximum oxygen consumption in middle-aged person.